Acute mental health presentations before and during the COVID-19 pandemic - Naaheed Mukadam; Andrew Sommerlad; Jessica Wright; Abigail Smith; Aleksandra Szczap; Solomis Solomou; Rohan Bhome; Roshan Thayalan; Esha Abrol; Golnar Aref-Adib; Lucy Maconick; Dominic Aubrey-Jones; et al. (BJPsych Open, 2021)
Background A number of community based surveys have identified an increase in psychological symptoms and distress but there has been no examination of symptoms at the more severe end of the mental health spectrum.